Investigating the role of survivin in mitochondrial health - Townley, Amelia (2017)
Survivin is a multi-functional protein with roles as both an apoptotic inhibitor and cell cycle regulator. Survivin is also one of the most tumour specific molecules, offering cancerous cells resistance to both chemotherapy and radiotherapy. It is localised to either the nucleus or cytoplasm, however a small pool with an unknown function is detected in cancerous cell lines within the mitochondria. Through the use of binding experiments we have unveiled two new binding partners of survivin, the tyrosine kinase c-Src and the glycerolphospholipid conversion enzyme phosphatidylserine decarboxylase. Firstly, we have found that the survivin1-10 NH2 terminus is a bona fide mitochondrial targeting sequence and allows for its binding to c-Src. Secondly, we have previously found that survivin binds to phosphatidylserine decarboxylase, and now we find that upon threonine 34 phosphorylation survivin inhibits phosphatidylethanolamine production within the mitochondria, causing drastic changes to mitochondrial architecture and cell growth. These novel molecular insights suggest that this multi-faceted protein may be even more diverse in its action than previously known. Furthermore, its current roles in cancer could further be clarified through the consideration of its influence upon membrane architecture, cell signalling and metabolism. We also provide insight to its contribution to metabolic disorders through the regulation of inner mitochondrial membrane integrity.